Baseline characteristics of the Nateglinide and Valsartan Impaired Glucose Tolerance Outcomes Research (NAVIGATOR) trial population: comparison with other diabetes prevention trials. - Krum, H; McMurray, J; Horton, E; Gerlock, T; Holzhauer, B; Zuurman, L; Haffner, S; Bethel, M; Holman, R; Califf, R (2010)
The Nateglinide and Valsartan Impaired Glucose Tolerance Outcomes Research (NAVIGATOR) trial is exploring two pharmacological strategies (nateglinide and valsartan, both alone and in combination) in the prevention of overt diabetes mellitus (DM) and the reduction of cardiovascular disease (CVD) in subjects at high risk for these events. In this analysis, we provide baseline characteristics of the randomized NAVIGATOR study population and contrast them with those from other trials of DM prevention. Key eligibility criteria include impaired glucose tolerance (IGT) and impaired fasting glucose (IFG), a history of CVD (in patients aged > or =50 years), and > or =1 cardiovascular risk factor (in patients aged > or =55 years). Baseline demographic characteristics, laboratory findings, cardiovascular risk factors, CVD history, and medication use are described and compared with other trials of DM prevention. The full analysis set of subjects (N = 9306) showed a clustering of risk factors consistent with the metabolic syndrome: high rates of hypertension (77.5%), dyslipidemia (44.7%), increased waist circumference (101.0 cm), and high body mass index (BMI) (47.5% with BMI > or =30 kg/m(2)). A minority of patients had a history of CVD (24.3%); of these, 11.7% had a history of myocardial infarction and most of the remainder had evidence of coronary artery disease. Subjects also had elevated blood pressure (BP) (predominantly systolic) (139.7/82.6 mm Hg), increased serum low-density lipoproteins cholesterol levels (3.27 mmol/L), and borderline elevation of triglyceride levels (1.97 mmol/L). Demographic data, BP, and lipid profiles in NAVIGATOR were similar to those of previous DM prevention trials, which were also based largely on meeting criteria for IGT. Medication use at baseline among NAVIGATOR subjects, which frequently included aspirin, beta-blockers, calcium channel blockers, diuretics, and lipid-lowering agents, reflects enhanced CVD risk. However, little prescribing of renin-angiotensin-aldosterone system blockers was observed, likely due to protocol exclusion criteria. In conclusion, the NAVIGATOR study comprises prediabetic subjects who typically have concurrent BP and metabolic disturbances and an enhanced risk of CVD, and are thus at higher risk for cardiovascular events than subjects in previous DM prevention trials.